Space-time dynamics of the burns in Brazil in the period 2003 to 2018 - Martins, Guilherme; Rosa, Ananda Santa; Setzer, Alberto; Rosa, Willian; Morelli, Fabiano; Bassanelli, Arielle [UNESP] (Revista Brasileira de Geografia Fisica, 2020)
In Brazil, vegetation fires are characterized by extensive and rapidly spreading fire lines that cause the mortality of flora and fauna species. Public policies were implemented to mitigate these damages, and for their correct enforcement it is necessary to understand the variability of the fire regime and the elements that affect it to improve prevention and combat strategies. In this sense, this work aimed to analyze the dynamics of burning in Brazil from 2003 to 2018 through the accumulated number of active fires and their anomalies as detected in satellite images with the precipitation climatology. The results showed that there are three spatial burning patterns in Brazil that relate with two precipitation systems: the Intertropical Convergence Zone and the South Atlantic Convergence Zone. A tendency to reduce the use of the fire was detected in most states; some indicated a stabilization of detection rates. The detections are still more frequent in drought periods, when the fires tend to contribute significantly to environmental degradation and to public budget expenditure in combat operations. It is up to the federal and state governments to invest in activities of enforcement, monitoring, environmental education and preventive management to reduce the use of fire in the country.
Dinâmica espaço-temporal das queimadas no Brasil no período de 2003 a 2018
Keywords: Active fire; Climatology precipitation; Public policies; Variability of fire